Organization and content of work of hospitals of different levels, accounting and analysis of their activity. Inpatient forms of care delivery : methodical recommendations to prepare 3–4 year students for practical classes for the discipline of «Social Medicine, organization of health care» [Electronic resourсe] - Bobrova, Oksana Vyacheslavivna; Tsukor, Nataliia Hryhorivna; Боброва, Оксана Вячеславівна; Цукор, Наталія Григорівна (Kharkiv : V.N. Karazin Kharkiv National University, 2024)
The presented methodical recommendations for students of higher medical education highlight topics devoted to an important section of social medicine and the organization of health care: the basics of organization, work and structure of hospitals of different levels, analysis of the activities of health care institutions. The methodical recommendations are developed on the basis of current regulatory documents on health care of Ukraine. Compiled in accordance with the educational and professional training program for students of higher medical education of the medical faculty of the 3rd–4th year of the university, qualification level Master, in the field of knowledge 22 «Health care», specialty 222 «Medicine». The material in the methodical recommendations is presented in English.

У представлених методичних рекомендаціях для здобувачів вищої медичної освіти висвітлені теми, присвячені важливому розділу соціальної медицини та організації охорони здоров`я: основам організації, роботи та структури стаціонарів різного рівня, аналізу діяльності закладів охорони здоров’я. Методичні рекомендації розроблені на основі діючих нормативних документів з охорони здоров'я України. Складені відповідно до освітньо-професійної програми підготовки здобувачів вищої медичної освіти медичного факультету 3–4 курсу університету, кваліфікаційного рівня Магістр, в галузі знань 22 «Охорона здоров’я», спеціальність 222 «Медицина». Матеріал у методичних рекомендаціях викладений англійською мовою.
Організація та зміст роботи стаціонарів різних рівнів, облік і аналіз їх діяльності. Стаціонарозамінні форми надання медичної допомоги : методичні рекомендації до практичних занять для здобувачів вищої медичної освіти 3–4 року навчання з дисципліни «Соціальна медицина, організація охорони здоров’я» [Електронний ресурс]
Електронне навчальне видання комбінованого використання. Можна використовувати в локальному та мережному режимі
Keywords: MEDICINE; clinic; healthcare facilities; activity analysis; hospital; medical assistance to the population; стаціонар; аналіз діяльності; заклади охорони здоров’я; лікарня; медична допомога населенню